Productivity, Cost-Benefit Analyses, Market Prices and Constraints to Poultry Farming in the Northern Districts of Bangladesh (Journal of Life and Earth Science, 2014)
A total of 6,41,004 chickens were produced by 10 farms, of which Cobb 500 (broilers) in P1 were the highest in number (2,43,000) and G1 yielded the lowest (10,117 Fayoumi, RIR and Sonali breeds). The most common chicken breed reared in the area was Cobb 500 (2,76,350) and the least common was ISA Brown (43,163). With regard to productivity, significant differences existed among the farms (F9, 103= 29.32; P P3 > P2 > P6 > P4 = P5). The overall profitability index (PI) values of government farms ranged between -0.09 and -0.13, whereas those of private farms between 0.18 and 0.52. Cobb 500 was the commonest but the least profitable breed, and Sonali was the most popular and cheapest one; and the growers achieved the maximum profit from Fayoumi. High feed cost, outbreak of diseases, inadequate supply of vaccines/medicines, lack of credit facilities and capital funding were recognized to be the major constraints to the poultry farming in the study area. DOI: http://dx.doi.org/10.3329/jles.v7i0.20117 J. Life Earth Sci., Vol. 7: 21-27, 2012